Varus knee osteoarthritis: how can we identify ACL insufficiency? - Waldstein, Wenzel; Merle, Christian (Knee surgery, sports traumatology, arthroscopy, 2015)
Purpose The aim of this prospective study was to determine the clinical value of lateral radiographs and corresponding MRI scans in the preoperative evaluation of the functional integrity of the anterior cruciate ligament (ACL) in a consecutive series of 78 patients (93 knees) with medial compartment osteoarthritis.MethodsAll knees received standardised radiographs and MRI imagery. The wear pattern on the lateral radiograph was described based on a modified Keyes classification. On MRI, the ACL and the percentage of intact posterior cartilage in relation to the anteroposterior tibia width were assessed.ResultsThe MRI showed an intact ACL in 23 (25 %) knees, evidence of ACL degeneration in 54 (58 %) knees and a complete ACL tear in 16 (17 %) knees. All knees with an intact ACL showed ≥14 % intact posterior cartilage on sagittal MRI scans, except for one knee. All knees with a torn ACL demonstrated <14 % intact posterior cartilage. Of the 54 knees with evidence of ACL degeneration, eight knees had <14 % intact posterior cartilage similar to the wear pattern present in knees with torn ACLs. Out of the 24 knees with a torn or degenerated ACL and <14 % intact posterior cartilage on MRI, 23 (96 %) knees demonstrated posterior bony erosion on corresponding lateral radiographs.ConclusionsThe assessment of intact posterior tibial cartilage on MRI and lateral radiographs helps to identify knees with functional ACL insufficiency. MRI with assessment of both the ACL morphology and the underlying tibial wear pattern appears to provide additional clinical benefit in cases in which the extent of posterior bony erosion on the lateral radiograph cannot be assessed with confidence.Level of evidenceDiagnostic study, Level II.
Gesehen am 21.02.2017